The impact of COVID-19 hospitalizations on nursing home admissions: a regional insight into long-term care and public health - Bandera, Alessandra; Colaneri, Marta; Galbussera, Alessia Antonella; Canuti, Marta; Dall’Olio, Lucia; Nobili, Alessandro; Puoti, Massimo; Marchetti, Giulia Carla; Piva, Simone; Plebani, Pierluigi; Raviglione, Mario; Gori, Andrea; et al. (Frontiers in Public Health, 2025)
BackgroundTo obtain the rate of admission to nursing homes (NHs) and to evaluate clinical characteristics and mortality rates of patients admitted to NHs after hospitalizations for COVID-19, compared to non-COVID-19 acutely hospitalized patients.MethodsWe analyzed administrative data from Lombardy, a Northen Italian region, in individuals aged ≥50 years who were hospitalized and discharged alive in 2018 for acute conditions or, between February 2020 and June 2022, for COVID-19. Outcomes included NH institutionalization rates within 180 post-discharge day and mortality following NH admission. Kaplan–Meier curves and Cox proportional hazard models adjusted for age, sex, and comorbidities were used to assess the risks.ResultsAmong 133,216 COVID-19 hospitalizations in 2020–2022 and 239,099 acute hospitalizations in 2018, institutionalization rates within 180 post-discharge days were similar (3.7% for both cohorts). However, COVID-19 patients had higher adjusted risks of institutionalization (HR 1.70; 95% CI 1.63–1.78) and mortality within 6 months after NH admission (HR 2.08; 95% CI 1.90–2.27). Differences were more pronounced when considering patients hospitalized during the first COVID-19 pandemic wave.ConclusionCOVID-19 hospitalization significantly increases the risks of admission to NHs and early mortality after institutionalization in older individuals compared to hospitalizations due to other acute conditions.